Corrosion engineering approach to rapidly prepare Ni(Fe)OOH/Ni(Fe)Sx nanosheet arrays for efficient water oxidation. Issue 9 (8th February 2023) - Chen, Mingyue; Li, Wenhui; Lu, Yu; Qi, Pengcheng; Wu, Hao; Liu, Gaofu; Zhao, Yue; Tang, Yiwen
Abstract : The heat generation in the corrosion solution was precisely controlled and successfully induced the hydrolysis of (NH2 )2 CS, and an alkaline environment was created for the rapid growth of Ni(Fe)OOH/Ni(Fe)S x . Abstract : The Ni–Fe composite catalyst has received in-depth research attention due to high intrinsic activity in electrochemical water splitting applications. Corrosion engineering is considered an effective strategy for preparing large-scale Ni–Fe composites to match industrial electrocatalytic electrolyzers. Here, we demonstrate an efficient corrosion strategy to prepare defect-rich Ni(Fe)OOH/Ni(Fe)S x nanosheet arrays on a NiFe foam within 10 min. The corrosion solution we proposed (containing (NH4 )2 S2 O8, (NH2 )2 CS, and FeCl3 ) has strong oxidizing properties, which releases a large amount of heat when it corrodes the Ni–Fe foam. The heat promotes the hydrolysis of (NH2 )2 CS and creates an alkaline environment for the rapid growth of Ni–Fe composites. Experimental results reveal that Ni(Fe)S x plays a crucial role in enhancing the oxygen evolution reaction performance of Ni(Fe)OOH/Ni(Fe)S x . Therefore, Ni(Fe)OOH/Ni(Fe)S x exhibits remarkable catalytic activity with low overpotentials of 227 and 313 mV to afford current densities of 10 and 1000 mA cm −2, respectively. Under 270 mV overpotential, the intrinsic catalytic activity of Ni(Fe)OOH/Ni(Fe)S x is 24.65-fold, 21.09-fold, and 52.21-fold that of FeOOH/FeS x, NiOOH/NiS x, and Ni(Fe)OOH, respectively. Moreover, large-scale Ni(Fe)OOH/Ni(Fe)S x electrode materials are prepared with a size of 10 × 10 cm 2 on a NiFe foam, implying the huge potential for practical applications. This work offers a new perspective on designing large-scale and highly active oxygen evolution catalysts.